PENINGKATAN PENGETAHUAN DAN PEMAHAMAN MAHASISWA DALAM MENGHADAPI TOEFL - Mika Andika Mika (JUPADAI : Jurnal Pengabdian Kepada Masyarakat, 2022)
TOEFL is an English proficiency test for foreign speakers whose certificates are recognized by thousands of educational institutions. The TOEFL certificate is not only a general requirement when you want to apply for scholarships both domestically and abroad or a requirement when applying for a job in a company. This is what causes the importance of the TOEFL certificate itself. Likewise with STIKES Citra Delima Bangka Belitung which is an administrative requirement to be able to complete his studies. However, the fact is that there are still many students of STIKES Citra Delima Bangka Belitung who do not know the TOEFL test, for example, students do not know the skill tested in the TOEFL test. The method used in this activity is by providing material, discussion, question and answer, and TOEFL test simulation. This activity was attended by 25 students who were held online by using Zoom meeting application. The results of this community service are the increasing ability of students in answering the TOEFL listening test questions by using the right tricks to answer the TOEFL listening test questions. This can be seen from the test results or the average score they get after participating in training activities and those who have never participated in TOEFL test training. The average score of the pre-test of listening skills before the service activity was carried out was 430 then the score of students' listening skills on the post-test after the activity was carried out by applying accurate methods and tricks increased to 500.